Satisfaction with e-Learning Systems during the COVID-19 Pandemic – A Comparative Study - Shahrokh Nikou; Seongcheol Kim; Chulmin Lim; Ilia Maslov (International Telecommunications Society (ITS), 2021)
Higher education institutions have increasingly been challenged in providing their core services of teaching and learning during the COVID-19 pandemic crisis. As such, many higher education institutions, if not all, have shifted towards distance learning and e-learning using learning management systems. In this paper, based on a comparative study among Finnish and South Korean university students, we aim to investigate students' level of satisfaction with e-learning during the COVID-19 pandemic. Building on a data set of 256 students from Finland and South Korea, the results of structural equation modelling (SEM) showed that all three of the COVID-19-related factors explored had a significant effect on students' level of satisfaction with e-learning. In addition, the SEM results showed that students' level of satisfaction with e-learning systems is affected by the level of students' information literacy skills as well as the information technology (quality and accessibility) used to access the e-learning systems. We also found interesting differences between Finnish and South Korean students, from the perspective of path model analysis. Theoretical and practical implications are discussed.
Keywords: 330